(untitled) (Development Service Industry Management, 2023)
The article highlights the specific definition of the term “economical safety”, which can be observed at different levels: micro-, meso- and macro-levels. On the macroeconomic level, the economic security of the state is determined by the aim of ensuring the stability and prosperity of the national economy, and includes the stability of the financial system, infrastructure development, the extent of unemployment, inflation, budget deficit, and sovereign wealt; on the meso-level - shows the progress of specific fields and regions of stability and the evolution of global and national economic issues, and conveys the diversification of industries, regional development, import and export dependency; on the micro-level - the capacity of individual enterprises and organizations to operate and compete in the marketplace, and covers financial stability, and covers financial stability, market responsiveness, manufacturing processes and supply chains. The author emphasizes on the relevance of the defensive approach when considering the concept of “economical business security” related to the current situation in Ukraine, which is characterized by the instability of the external environment and large-scale military actions. The defense approach conveys an emphasis on protecting against possible threats and risks, rather than on the active development and recovery of opportunities. Thus, under the concept of economic security of enterprise, the author understands the protection of all spheres of activity and interests of enterprise from the negative influence of external and internal factors. The concept of economic security is closely related to the concepts of risk, challenge, threat, and danger. Therefore, the article analyzes these concepts and draws the appropriate conclusions, a separate one: risk is a general concept that indicates a potential danger, but does not specify how exactly this danger manifests itself; a challenge is a specific aspect or situation that creates opportunities or a threat and may be part of the overall risk; threat is a specific cause of danger; danger is a specific negative danger is a specific negative consequence resulting from the specified threat the identified threat. The scheme is given, made on the basis of the author conclusions, that reflects the manifestation and interrelation of destructive factors (risk, challenge, threat, danger). In addition, risk assessment methods are provided.